The impact of tourists’ perceptions of space-launch tourism: An extension of the theory of planned behavior approach - Wang, L.; Fu, C. F.; Wong, P. P. W. *; Zhang, Qi (Routledge, 2021)
Prior studies on space tourism have mainly investigated tourists’ engagement in outer space tourism activities. There is no research undertaken as yet related to tourists’ perception toward indoor space tourism (i.e., space-launch tourism). The aim of this study is to examine the relationship between attitude, subjective norm, perceived behavioral control, hedonic motivation, and intention toward space-launch tourism activities using the Wenchang spacecraft launch site as the tourism destination. An integrated conceptual research model was proposed based on the theory of planned behavior model. A web-based survey questionnaire was developed where a total of 444 questionnaires were ultimately collected followed by subsequent empirical testing of the postulated hypotheses, using SPSS and Structural Equation Modeling (SEM). The results suggested that attitude, subjective norm, perceived behavioral control and hedonic motivation positively influence intention. Subjective norm also displayed a significant positive influence on attitude, while attitude played a partial mediation role between subjective norm and intention. The findings indicated that the proposed model has more predictive capacity compared to original theory of planned behavior model. The theoretical and practical implications of the results were also discussed, including limitations of the research.